(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This investigation primarily deals with the probable causes of in-service damage of head gear pulley in a coal mines. In this paper different component of conveyor pulley (shell, end disk, hub, and shaft) failure and the stresses generated on them are discussed. This paper presents proposed methodology meshing, material property and fixed support. In this work Implement new alloy spokes by replace alloy spokes.The proposed work is to design of head gear pulley is based on the stress criteria, according to design specification the ultimate tensile strength. In that the two new designs is proposed in gear head pulley in three different spokes material is used the first material is used is steel, second is titanium alloy and last is magnesium alloy. The result obtained the stress value is under the standard stress limit as well as reduces the overall weight of head gear pulley.